2015
DOI: 10.3171/2015.1.peds14511
|View full text |Cite
|
Sign up to set email alerts
|

Use of a formal assessment instrument for evaluation of resident operative skills in pediatric neurosurgery

Abstract: OBJECT Currently there is no standardized tool for assessment of neurosurgical resident performance in the operating room. In light of enhanced requirements issued by the Accreditation Council for Graduate Medical Education’s Milestone Project and the Matrix Curriculum Project from the Society of Neurological Surgeons, the implementation of such a tool seems essential for objective evaluation of resident competence. Beyond compliance with governing body guidelines, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Data were then stratified by faculty versus resident, postgraduate year level, and difficulty of procedure. 37 Although there were questions regarding the construct validity and reliability of this method, 48 the study did demonstrate the feasibility of using OSATS for neurosurgical resident evaluation.…”
Section: Objective Structured Assessment Of Technical Skillsmentioning
confidence: 90%
See 2 more Smart Citations
“…Data were then stratified by faculty versus resident, postgraduate year level, and difficulty of procedure. 37 Although there were questions regarding the construct validity and reliability of this method, 48 the study did demonstrate the feasibility of using OSATS for neurosurgical resident evaluation.…”
Section: Objective Structured Assessment Of Technical Skillsmentioning
confidence: 90%
“…Supervised, interpersonal mentorships developed through direct apprenticeship, coaching, and training in the operating room are a key component of neurosurgical training. 18,37,53 Unfortunately, opportunities to operationalize this type of teaching experience are increasingly difficult because of Accreditation Council for Graduate Medical Education (ACGME) resident duty-hour limitations, 41,44,58 financial pressures to be efficient in the operating room, 8,43,72 and the understandable emphasis on highquality care with low complication rates and short hospital stays. It is therefore imperative that surgical education also evolve to reflect an equal degree of efficiency and that effective methods for teaching skills outside the operative setting be employed.…”
Section: Teaching Learning and Assessment In The Operating Roommentioning
confidence: 99%
See 1 more Smart Citation
“…1 Simulation training can increase proficiency and allow learners to reach milestones set forth by accrediting agencies. 2 Furthermore, simulation allows for appreciation of relevant neuropathology and anatomy that may be pertinent intraoperatively. 3 In particular, endoscopic skull base approaches, which have a steep learning curve, can be practiced in a controlled and replicable environment.…”
Section: Introductionmentioning
confidence: 99%
“…Lower performing learners may not have insight into their low performance; conversely, higher performing learners may be more aware of their deficits than their strengths [11,13,14]. A few studies with very specific learner types and environments have shown good correlation between expert assessments and learner self-assessments, but these have been the exception rather than the rule [15][16][17][18][19]. Furthermore, the success reported in these environments may be due to a focus on self-monitoring rather than global self-assessment [20].…”
mentioning
confidence: 99%